Effect of Mycobacterium tuberculosis and its components on macrophages and the release of matrix metalloproteinases. - Chang, J. C. (1996)
BACKGROUND: Pulmonary tuberculosis is associated with caseating necrosis, parenchymal lung destruction, and cavity formation. It was hypothesised that tuberculous lung destruction is mediated, at least in part, by the participation of matrix metalloproteinases released by mononuclear phagocytes. METHODS: Cells of the myelomonocytic leukaemia cell line THP-1 were incubated with lipoarabinomannan (LAM), the major antigenic cell wall component, and with Mycobacterium tuberculosis and analysed by Northern blot analysis. Two patients with active cavitary tuberculosis also underwent bronchoalveolar lavage and the cells were analysed by Northern blotting. RESULTS: Incubation of THP-1 cells with LAM resulted in the stimulated release of matrix metalloproteinase-9 (MMP-9), a 92 kDa gelatinase, by 24 hours in a dose-dependent fashion. In addition, Northern analysis revealed that LAM upregulated the gene for MMP-9 by 24 hours, but not the gene for the 72 kDa gelatinase MMP-2. Heat killed M tuberculosis H37Ra also upregulated the MMP-9 gene. Bronchoalveolar lavage of the two patients with active cavitary tuberculosis showed striking upregulation of the MMP-9 gene compared with a normal control using Northern analysis. LAM also upregulated the type I interstitial collagenase (MMP-1) gene by 24 hours in both THP-1 cells and peripheral blood monocytes. CONCLUSIONS: These data suggest that M tuberculosis and its major cell antigenic component, LAM, stimulate the release of MMP-9 and upregulate the expression of genes for MMP-1 and MMP-9. It is possible that M tuberculosis and its components contribute directly to cavity formation by their ability to stimulate macrophages to release matrix metallo-proteinases that digest collagens I-IV, and indirectly by stimulating the release of the cytokines interleukin 1 beta and tumour necrosis factor alpha that induce fibroblasts to amplify the release of matrix metalloproteinases.